2020
DOI: 10.1186/s41240-020-0148-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of three different dietary plant protein sources as fishmeal replacers in juvenile whiteleg shrimp, Litopenaeus vannamei

Abstract: Background: As the cost of fishmeal continues to rise, there will be a need to optimize the diet by minimizing dietary fishmeal inclusion in aquafeed. In this study, a 7-week experiment was conducted to evaluate soybean meal, fermented soybean meal (soytide), and sesame meal as fishmeal replacers in whiteleg shrimp, Litopenaeus vannamei.Methods: A 30%-based fishmeal diet was considered as control (CON), six other diets were prepared by replacing 20% or 40% of fishmeal with soybean meal (SB 20 and SB 40 ), ferm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 21 publications
2
17
0
2
Order By: Relevance
“…This is in agreement with the report of good survival rate (>87%) in shrimp fed 25-100 g/kg rapeseed meal [28]. In other growth trials, the inclusion of 20-40% sesame meal and 1-10% sunflower cake to shrimp diets also led to good survival rates and health conditions [29,30]. Our results show that 25-35% of the peptides released from the five oilseeds were potentially toxic to fish (Table 2).…”
Section: Toxicity Of Peptidessupporting
confidence: 92%
“…This is in agreement with the report of good survival rate (>87%) in shrimp fed 25-100 g/kg rapeseed meal [28]. In other growth trials, the inclusion of 20-40% sesame meal and 1-10% sunflower cake to shrimp diets also led to good survival rates and health conditions [29,30]. Our results show that 25-35% of the peptides released from the five oilseeds were potentially toxic to fish (Table 2).…”
Section: Toxicity Of Peptidessupporting
confidence: 92%
“…Similarly, Zhang et al, (2020) showed that GOT and GPT in the hepatopancreas of white shrimp were reduced with increasing FM replacement by SBM. On the contrary, Bae et al, (2020) showed that GOT and GPT in white shrimp plasma did not differ with FM replacement by SBM and fermented SBM.…”
Section: Discussionmentioning
confidence: 93%
“…The present result showed that SAP0 contained lower activities of LZM, AKP, and ACP, compared to the FM group. Related researches have suggested that dietary fishmeal replacement with plant protein would decrease the nonspecific immunity in aquatic animals, which was verified in hybrid grouper [54] and Pacific white shrimp [55]. From another perspective, the activities of LZM, AKP, and ACP showed an elevated trend in the SAP-treated groups.…”
Section: Discussionmentioning
confidence: 79%